Effects of humidity on variation of negative corona‐generated space charge in rod to plane electrode. Issue 16 (18th December 2018) - Bian, Xingming; He, Zichen; Zhu, JunYu; Pi, Xinan; Wan, Shuwei; Qi, Lei
Abstract : The variation of negative corona‐generated space charge related to the humidity has been systematically calculated and analysed by computational approaches. A negative fluid model in which the humidity could be adjusted was established to calculate the charged‐particle density and electric field under different applied voltages. The continuity equations were solved by a flux‐corrected transport algorithm and the Poisson equation was computed by the successive over relaxation method. The variations of important parameters due to humidity were discussed including ionisation coefficient, attachment coefficient, effective ionisation coefficient and electron generation rate. Each of them increases with the rise in relative humidity (RH). The particles densities of electrons, positive ions and negative ions when RH is 50, 80 and 90% were also calculated, respectively, which decreased as RH increased.